2020
DOI: 10.1155/2020/5710419
|View full text |Cite
|
Sign up to set email alerts
|

Signal Game Analysis on the Effectiveness of Coal Mine Safety Supervision Based on the Affective Events Theory

Abstract: The main cause of coal mine safety accidents is the unsafe behavior of miners who are affected by their emotional state. Therefore, the implementation of effective emotional supervision is important for achieving the sustainable development of coal mining enterprises in China. Assuming rational players, a signaling game between miners (emotion-driven and judgement-driven) and managers is established from the perspective of Affective Events Theory in order to examine the impact of managers’ emotions on coal min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The mental status of individual workers can also influence their unsafe behaviors, which mainly include safety attitude, safety awareness, work pressure and risk perception. Yang et al ( 37 , 38 ) reported that the main cause of coal mine safety accidents was the unsafe behavior of miners affected by emotions. When workers are in a bad mental state, they are prone to unsafe behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The mental status of individual workers can also influence their unsafe behaviors, which mainly include safety attitude, safety awareness, work pressure and risk perception. Yang et al ( 37 , 38 ) reported that the main cause of coal mine safety accidents was the unsafe behavior of miners affected by emotions. When workers are in a bad mental state, they are prone to unsafe behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also optimized the occupational safety compliance control system of coal mining enterprises by using the game method. Yang et al ( 37 ) established a signal transmission game between miners and managers based on the game theory model to test the influence of managers' emotions on miners' behaviors. Meng et al ( 75 ) reviewed relevant articles on game theory and safety management during 2010–2019 and affirmed that the application of game theory in safety management research is conducive to determine the causes and motivations of unsafe behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e effective supervision of coal miners' emotions is an important means to achieve coal mine safety [40]. When certain conditions are met, all parties in the game can reach the ideal stable state [41].…”
Section: Literature Reviewmentioning
confidence: 99%
“…e research of organizational relationships usually adopts game methods. Yang et al examined the impact of managers' emotions on miners' behavior using a bilateral signaling game driven by emotion and judgment [23]. Yu et al described the asymmetry of the game interests between managers and miners with the system dynamics method [24].…”
Section: Human Factors In Coal Mine Safety and Healthmentioning
confidence: 99%